Faktor – Faktor Sosial Ekonomi Yang Mempengaruhi Pendapatan Usahatani Tanaman Hias Mawar di Desa Sidomulyo Kota Batu Malang - Ibrahim Hasan; Dwi Susilowati; Moch. Noerhadi Sudjoni (Program Studi Agribisnis, 2019)
ABSTRACTThe purpose of this study was to analyze the income and efficiency of ornamental rose farming in Sidomulyo Village, to analyze socio-economic factors that affect the income of rose ornamental plant farming in Sidomulyo Village. Location selection was done by purposive method carried out on Sidomulyo Village farmers in Batu City. Sampling was done by simple random sampling. The analysis used in this study is the advantage of multiple linear regression functions. The results of the study revealed that the average income of farmers in Sidomulyo Village for roses ornamental farming was Rp. 22,666,373 per m2 per one planting period. The results of the study show that the R / C ratio of rose ornamental plants is said to be feasible to develop because of the R / C ratio ≥ 1. The R / C Ratio ornamental plant farming is 5.22, which means that roses in Sidomulyo Village are suitable for farming. developed. The results of multiple linear regression analysis, the independent variables that influence profits are Seed Costs and Land Area at a 90% confidence level. While the independent variables that have no effect on income are Age, Education Level, Fertilizer Cost, Drug Costs, Medicinal Experience and Labor.Keywords: income, efficiency, influencing factors